2017
DOI: 10.1371/journal.pone.0170936
|View full text |Cite
|
Sign up to set email alerts
|

Activity Regulation by Fibrinogen and Fibrin of Streptokinase from Streptococcus Pyogenes

Abstract: Streptokinase is a virulence factor of streptococci and acts as a plasminogen activator to generate the serine protease plasmin which promotes bacterial metastasis. Streptokinase isolated from group C streptococci has been used therapeutically as a thrombolytic agent for many years and its mechanism of action has been extensively studied. However, group A streptococci are associated with invasive and potentially fatal infections, but less detail is available on the mechanism of action of streptokinase from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…For example, very high inhibition rate constants (of the order of 10 7 mol L −1 s −1 ) are often quoted for α2AP and PAI‐1, but these are modulated by fibrinogen and fibrin in vivo . Solution studies are definitely easier to perform than studies in a fibrin matrix and are useful for plasminogen activators such as urokinase (uPA) or therapeutic streptokinase (but note, streptokinase variants from other streptococcus strains do interact with fibrinogen and fibrin ). Experience has shown that caution is needed when using tPA with soluble stimulators such as cyanogen bromide fragments of fibrinogen , compared with fibrin , as the kinetics of binding and plasminogen activation are different.…”
Section: Plasminogen Activators and Plasmin In Purified Systemsmentioning
confidence: 99%
“…For example, very high inhibition rate constants (of the order of 10 7 mol L −1 s −1 ) are often quoted for α2AP and PAI‐1, but these are modulated by fibrinogen and fibrin in vivo . Solution studies are definitely easier to perform than studies in a fibrin matrix and are useful for plasminogen activators such as urokinase (uPA) or therapeutic streptokinase (but note, streptokinase variants from other streptococcus strains do interact with fibrinogen and fibrin ). Experience has shown that caution is needed when using tPA with soluble stimulators such as cyanogen bromide fragments of fibrinogen , compared with fibrin , as the kinetics of binding and plasminogen activation are different.…”
Section: Plasminogen Activators and Plasmin In Purified Systemsmentioning
confidence: 99%
“…Secreted or surface-located microbial proteases often possess an ability to activate or inactivate particular enzymatic components of these proteolytic cascades or to degrade dedicated proteinase inhibitors, thus leading to deregulation of the physiological functionality of such systems (Maeda & Yamamoto, 1996;Potempa et al, 2000;Kozik et al, 2015a;Gogol et al, 2016;Huish et al, 2017). Moreover, a great variety of bacterial or fungal surface-exposed proteins were repeatedly reported to be involved in the interactions with human plasma proteins (Smeesters et al, 2010;Rapala-Kozik et al, 2011;Wollein Waldetoft et al, 2012;Castiblanco-Valencia et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is naturally produced by the strains of β-hemolytic streptococci which utilize it for overcoming the host’s defensive fibrin barrier and for promoting bacterial metastasis and colonization [183,184]. There are several streptokinases from different streptococci which vary in their structure, but the only variant of streptokinase currently used as a thrombolytic agent originates from the group C streptococci (streptokinase SK-H46A from Streptococcus equisimilis strain H46A) and lacks a significant stimulation by fibrin [185,186]. Despite its moderate half-life in vivo (approximately 10 min) and significantly lower cost, the largest disadvantages are the lack of fibrin specificity and immunogenicity due to its bacterial origin [47,[187], [188], [189]].…”
Section: Streptokinasementioning
confidence: 99%
“…Due to the α domain, streptokinase does not require fibrin and activates plasminogen independently [186,194,200]. Stimulating experiments confirmed that neither fibrin nor fibrinogen had stimulatory effects on activation, preventing targeted thrombolysis on the surface of fibrin clots [185,186]. The activation independent of fibrin can lead to bleeding complications which represents one of the main drawbacks of the currently used streptokinase variant.…”
Section: Streptokinasementioning
confidence: 99%